History of preoperative therapy for pancreatic cancer and the MD Anderson experience. Issue 6 (8th April 2021) - Gaskill, Cameron E.; Maxwell, Jessica; Ikoma, Naruhiko; Kim, Michael P.; Tzeng, Ching‐Wei; Lee, Jeffrey E.; Katz, Matthew H. G.
Abstract: Systemic chemotherapy improves the survival of patients who undergo pancreatectomy, but whether chemotherapy should be delivered before or after surgery remains debated. At The University of Texas MD Anderson Cancer Center, localized pancreatic ductal adenocarcinoma (PDAC) has been preferentially treated with preoperative therapy—a practice supported by a robust history of institutional and national trials. In the following review, we discuss the historical use of perioperative therapy, our experience with it at MD Anderson Cancer Center and internationally, and the future of treatment and trials for PDAC.